A comparison of undergraduate marketing curricula by type of accreditation. (3rd June 2021) - Herrington, J. Duncan; Lollar, James G.
Previous studies of coursework required for marketing degrees have been limited to programs accredited by Association to Advance Collegiate Schools of Business (AACSB International). Given that AACSB accreditation applies to less than one-third of all four-year business programs in the US, previous results are limited in scope. Research reported here draws current data from a broader selection of programs holding different types of accreditation thus providing a more complete view of coursework required by marketing programs. The findings reported here show little change over time for programs holding accreditation by AACSB International, yet significant differences between programs holding different types of accreditation.